PEMBUATAN ETANOL DARI BUAH MENGKUDU - Indrati Utami, Lucky (Jurnal Teknik Kimia, 2009)
Mengkudu represent all purppose crop, a lot of type of amendable product from root, bar, leaf, and also its fruit.At fruit mengkudu have content of carbohydrate as much 51,67 gr. With obstetrical existence the carbohydrate enable to be exploited permanent upon which produce ethanol. Intention of this research is determine condition of best process making of ethanol with raw material of fruit mengkudu.Ethanol yielded to be obtained heatedly of fruit mengkudu liquid by HCL 0,4 N in neck gourd three as hydrolysis process, so that got the sugar rate equal to 8,23%. Hereinafter, can be made ferment media from sugar liquid result of hydrolysis enhanced by a starter volume at spanning : 4- 12%. Later;then ferment as according to variation time of between 24 - 72 clock. Liquid of result of the ferment dissociated by distilatation, temperature taken care of 80ºC.Result of biggest ethanol obtained when ferment 60 clock, addition of volume starter 10% with ethanol rate = 6,24 %.Keyword : Ferment , Hydrolysis, mengkudu , Saccharomyces Cerevisiae, Ethano